(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effect of bowel preparation timing on the quality of colon cleansing in patients undergoing colonoscopy at Can Tho University of Medicine and Pharmacy Hospital. Methods: A comparative study was conducted on 192 patients who were divided into two groups (A and B) based on the timing of bowel preparation at Can Tho University of Medicine and Pharmacy Hospital. The quality of bowel cleansing was assessed using the Boston bowel preparation scale for each colonic segment and the entire colon. Results: There were no statistically significant differences between the 2 groups regarding baseline characteristics (p > 0.05). The mean Boston bowel preparation scale score in the right colon was significantly higher in group A compared to group B (2.52 ± 0.583 vs. 2.31 ± 0.573, p = 0.031). The proportion of “excellent” bowel preparation (Boston bowel preparation scale = 3) in the right colon was also significantly higher in group A than in group B (56.3% vs. 36.8%, p = 0.018). However, there were no statistically significant differences in the overall “adequate” bowel preparation rates between the 2 groups across all colonic segments. Conclusion: The timing of bowel preparation has an impact on the quality of colon cleansing, particularly in the right colon.